Bilateral Incomplete Atypical Femur Fractures with Severe Bowing Treated Using Elastic Intramedullary Nails: A Case Report. Issue 2 (8th April 2022) - Okubo, Naoki; Yoshida, Takashi; Tanaka, Kazuya; Asano, Mizuki; Nakazawa, Taku; Ohara, Masato; Hosoi, Kunihiko; Takahashi, Kenji
Abstract : Case: A 77-year-old woman with bilateral symptomatic atypical femoral fractures (AFFs) and severe anterolateral bowing due to long-term bisphosphonate administration was treated using stainless elastic intramedullary nails. Weight-bearing pain disappeared immediately after surgery. Radiographs obtained 1 year postoperatively showed fracture healing. Conclusion: Although intramedullary nail insertion has been recommended for symptomatic incomplete AFFs, in cases of severe bowing, rigid nail insertion was often challenging, and the complication rates were higher than those with mild bowing. The advantage of our method is easy insertion, suggesting effective treatment.